Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part Iv.-writing and Printing Papers from Helioteres isora, Linn. (Maror phal) - Bhat, R. V.; Singh, Man Mohan (Indian Forester, 1951)
Laboratory experiments on the production of chemical pulps from Helicteres isora, Linn. (marar phal) are described. Results of pilot plant experiments on the production of chemical pulps and writing and printing papers are included. Admixture of chemical pulps from marar phal with long-fibred chemical pulps such as sabai grass pulp gave writng paper with higher strength properties. It has recently been reported that the bark of Helicteres isora has been found suitable as a substitute for jute in the preparation of gunny bags. The wood of this species should, therefore, be available at a cheap price. Besides, there is no other use for this wood.